Structural Integrity Study Of Ultra-Fine Solder Joint Using Microscopy Investigation - Zahit, Mohd Amier Hasief Mat (Universiti Sains Malaysia, 2017)
The electronic industries are changing the solder used from the lead solder to the lead-free solder. The elimination of lead solder is done due to the new laws and restrictions. The lead-free solder is extensively used in the electronic assemblies and there is also concerns about the lead-free solder reliability. Solder joints in electronic products are used as interconnection material for enabling electrical, thermal and mechanical function in the electronic packaging. Addition of nano particles in the solder joint is to investigate the relation between the percentage and the quality of the solder joint. The quality of the solder joints is one of the most important aspect that we need to consider to make a good solder joint. The hardness test of the solder joint is to know what is the relation between hardness and the percentage of the nano particles in solder joint. Three types of solder joints that contain 0.01%, 0.05%, and 0.15% of Fe2O3 (Feric Oxide) are used in the experiment with small (01005), medium (0603) and big (0805) size of the component.